COPD - Kerstjens, Huib AM (BMJ Publishing Group, 2008)
INTRODUCTION: Chronic obstructive pulmonary disease (COPD) is a disease state characterised by airflow limitation that is not fully reversible. The airflow limitation is usually progressive and associated with an abnormal inflammatory response of the lungs to noxious particles or gases. Classically, it is thought to be a combination of emphysema and chronic bronchitis, although only one of these may be present in some people with COPD. The main risk factor for the development and deterioration of COPD is smoking. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of maintenance drug treatment in stable COPD? What are the effects of maintenance drug treatment in stable COPD? What are the effects of non-drug interventions in people with stable COPD? We searched: Medline, Embase, The Cochrane Library, and other important databases up to February 2007 (Clinical Evidence reviews are updated periodically, please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 83 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: alpha(1) antitrypsin, antibiotics (prophylactic), anticholinergics (inhaled), beta(2) agonists (inhaled), corticosteroids (oral and inhaled), general physical activity enhancement, inspiratory muscle training, maintaining healthy weight, mucolytics, oxygen treatment (long-term domiciliary treatment), peripheral muscle strength training, psychosocial and pharmacological interventions for smoking cessation, pulmonary rehabilitation, and theophylline.